Perovskite-silicon tandem cell based on laser-assisted encapsulation and method of manufacture
Patent Information
- Application Number
- CN202510746241.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-05
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-06-05
AI Technical Summary
但目前针对该叠层电池的封装技术还不够完善,传统的封装材料和工艺可能无法满足其特殊的结构和性能要求,存在封装材料与叠层电池之间的相容性问题、封装过程中的工艺精度控制难题以及长期使用过程中的可靠性封装挑战等
[0017]1、本发明采用激光边缘隔离技术能够在叠层电池顶部钙钛矿电池活性层切面四周形成保护槽,阻隔外界水氧侵蚀破坏,降低钙钛矿吸收层分解的风险,延长叠层电池的使用寿命。另外,保护槽之间残留区域的钙钛矿吸收层也能够避免激光发出的能量直接作用于晶硅底电池,降低激光刻蚀过程对晶硅底电池的损伤,显著提升叠层电池的稳定性。
Smart Images

Figure CN120711934B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar cell technology, and particularly relates to a perovskite-silicon tandem solar cell based on laser-assisted encapsulation and its preparation method. Background Technology
[0002] In recent years, perovskite solar cells have attracted widespread global attention due to their high efficiency, low cost, and simple fabrication process. The photoelectric conversion efficiency of small-area single-junction perovskite cells has rapidly increased from 3.8% in 2009 to over 26%. Compared with traditional thin-film solar cells (such as copper indium gallium selenide and cadmium telluride), perovskite solar cells have higher conversion efficiency, simpler fabrication processes, and lower production costs, and are therefore considered one of the thin-film solar cell technologies with the best prospects for industrialization.
[0003] By adjusting the perovskite composition ratio, the spectral response cutoff wavelength of perovskite solar cells can be controlled, making them ideal top-layer absorber materials for tandem solar cells. Combining perovskite solar cells (top cells) with crystalline silicon solar cells (bottom cells) to form a "perovskite / crystalline silicon" tandem solar cell structure can achieve distributed absorption of the solar spectrum, potentially leading to higher conversion efficiencies. Currently, the efficiency of small-area perovskite / silicon heterojunction tandem solar cells exceeds 34%. In the actual research and application of perovskite-crystalline silicon tandem solar cells, stability has become one of the key factors restricting their development. On the one hand, perovskite materials are inherently sensitive to environmental factors such as humidity, temperature, and light intensity. Long-term exposure to these complex environmental conditions can easily cause phase transitions, decomposition, or defects in the perovskite layer, leading to a decline in cell performance. On the other hand, the interfacial interactions between the layers within the tandem solar cell are complex. Under different operating conditions and stresses, problems such as increased charge recombination at the interfaces and poor contact may occur, further affecting the stability, lifespan, and encapsulation of the cell. Good encapsulation can effectively prevent the intrusion of harmful substances such as moisture and oxygen, slow down the degradation rate of perovskite materials, and protect the delicate internal structure of the battery, maintaining good contact between layers and electrical performance. However, current encapsulation technology for this type of tandem battery is not yet perfect. Traditional encapsulation materials and processes may not meet its special structural and performance requirements, presenting challenges such as compatibility issues between encapsulation materials and the tandem battery, difficulties in controlling process precision during encapsulation, and reliability challenges during long-term use. Furthermore, perovskite-crystalline silicon tandem batteries also face the risk of short circuits. During the fabrication of tandem batteries, even minute defects, impurity particles, or misaligned deposits can create localized short circuit paths within the battery, leading to a significant drop in output power, accelerated aging and damage, and severely impacting normal operation. Therefore, reducing the short-circuit risk of perovskite-crystalline silicon tandem batteries and improving their operational reliability are crucial for advancing tandem batteries from laboratory research to large-scale commercial applications. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies by providing a laser-assisted encapsulation method for perovskite-crystalline silicon tandem solar cells. This method combines laser edge isolation technology and internal encapsulation buffer layer deposition technology to achieve tight sealing of the perovskite layer at the edge of the tandem solar cell. The excellent sealing performance suppresses the corrosion of the top metal gate by halide ions in the perovskite absorber layer and effectively blocks the erosion of the perovskite layer by water and oxygen in the air, significantly improving the stability and lifespan of the tandem solar cell. Furthermore, severe mask misalignment deposition exists between the window layer and the interconnect layer in tandem solar cells, leading to a significant risk of short-circuit contact. The laser-assisted encapsulation technology provided by this invention can effectively isolate the electrical connection between the window layer and the interconnect layer to achieve complete insulation, eliminating the risk of short circuits inside the tandem solar cell, significantly improving the yield of tandem solar cell fabrication, and saving substantial production costs. The laser-assisted tandem solar cell encapsulation process provided by this invention is simple and significantly promotes the industrialization of perovskite-crystalline silicon tandem solar cells.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: As a first aspect, a perovskite-silicon tandem solar cell based on laser-assisted encapsulation is provided. The perovskite-silicon tandem solar cell, from bottom to top, comprises a first metal gate, a silicon substrate, an interconnect layer, a first charge transport layer, a perovskite light-absorbing layer, a second charge transport layer, an inner encapsulation buffer layer, a transparent window layer, and a second metal gate. The inner encapsulation buffer layer covers the interconnect layer, the first charge transport layer, the perovskite light-absorbing layer, the second charge transport layer, and the second charge transport layer, and the side lengths of the interconnect layer, the first charge transport layer, the perovskite light-absorbing layer, and the second charge transport layer covered by the inner encapsulation buffer layer are all smaller than the side length of the silicon substrate.
[0006] Furthermore, the side lengths of the interconnect layer and the transparent window layer are smaller than the side lengths of the crystalline silicon bottom cell, the first charge transport layer, the perovskite light-absorbing layer, and the second charge transport layer.
[0007] As a second aspect, the present invention also provides a method for fabricating a perovskite-silicon tandem solar cell based on laser-assisted encapsulation, the method comprising the following steps:
[0008] A first metal gate is fabricated on the back side of a crystalline silicon substrate cell; an interconnect layer, a first charge transport layer, a perovskite light-absorbing layer, and a second charge transport layer are sequentially fabricated on the front side of the crystalline silicon substrate cell; a laser is used to perform a first edge isolation etching on the four sides of the front side of the cell; an inner encapsulation buffer layer, a transparent window layer, and a second metal gate are sequentially fabricated on the etched front side of the cell; a laser is used to perform a second edge isolation etching on the four sides of the front side of the cell, thus obtaining a complete laser-assisted encapsulated perovskite crystalline silicon tandem cell.
[0009] Furthermore, the edges of the interconnect layer and transparent window layer patterns are e1 and e2 away from the edge of the crystalline silicon substrate cell, respectively, where 0 < e1 = e2 < side length of the crystalline silicon substrate cell / 2.
[0010] Furthermore, the edges of the first edge isolation etching are c1 and c2 away from the edges of the interconnect layer pattern, where 0 < c1 = c2 < e1.
[0011] Furthermore, the widths of the first edge isolation etching are b1 and b2, where 0 < b1 = b2 < e1.
[0012] Furthermore, the edges of the second edge isolation etching are d1 and d2 away from the edges of the interconnect layer pattern, where c1 < d1 = d2 < e1.
[0013] Furthermore, the widths of the second edge isolation etching are a1 and a2, where 0 < a1 = a2 = e1 - d1 < e1 - c1.
[0014] Furthermore, the inner encapsulation buffer layer is one or more composites of tin oxide, zinc oxide, nickel oxide, molybdenum oxide, aluminum oxide, silicon oxide, titanium oxide, vanadium oxide, chromium oxide, manganese oxide, magnesium oxide, lead oxide, germanium oxide, cobalt oxide, cuprous oxide, gallium oxide, zirconium oxide, niobium oxide, indium oxide, antimony oxide, cerium oxide, tantalum oxide, and tungsten oxide.
[0015] Furthermore, the inner encapsulation buffer layer is deposited by atomic layer deposition, chemical vapor deposition, or physical vapor deposition, preferably atomic layer deposition, with a thickness of 0.1–3000 nm.
[0016] The beneficial effects of this invention are:
[0017] 1. This invention employs laser edge isolation technology to form protective grooves around the cut surface of the perovskite active layer on the top of the tandem solar cell. This prevents external water and oxygen erosion and damage, reduces the risk of perovskite absorber layer decomposition, and extends the lifespan of the tandem solar cell. Furthermore, the perovskite absorber layer remaining in the area between the protective grooves also prevents the energy emitted by the laser from directly affecting the crystalline silicon bottom cell, reducing damage to the crystalline silicon bottom cell during laser etching and significantly improving the stability of the tandem solar cell.
[0018] 2. This invention combines atomic layer deposition (ALD) with internal encapsulation buffer layer technology and laser fine scribing technology to reduce the short-circuit risk of tandem solar cells. It can prevent the interconnect layer from conducting with the transparent window layer, suppress carrier recombination, ion migration and metal gate corrosion in the perovskite light-absorbing layer, reduce the mask deposition difficulty of the interconnect layer and transparent window layer, and achieve excellent encapsulation effect while ensuring the efficiency of perovskite crystalline silicon tandem solar cells.
[0019] 3. The present invention uses laser-assisted encapsulation of perovskite-silicon tandem solar cells to achieve high stability without reducing cell efficiency, effectively reducing the encapsulation process difficulty and cost of tandem solar cells, and can be used for large-scale mass production. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of the laser-assisted encapsulated perovskite-silicon tandem solar cell structure provided by the present invention;
[0022] Figure 2 A flowchart of the laser-assisted encapsulation perovskite-silicon tandem solar cell fabrication process provided by the present invention;
[0023] Figure 3 This is a schematic cross-sectional view of the laser-assisted encapsulated perovskite-silicon tandem solar cell in Embodiment 1 of the present invention;
[0024] Figure 4 This is a schematic cross-sectional view of the perovskite-silicon tandem solar cell in Comparative Example 1 of the present invention;
[0025] Figure 5 This is a schematic cross-sectional view of the perovskite-silicon tandem solar cell in Comparative Example 2 of the present invention;
[0026] Figure 6 This is a surface image of the edge isolation etching region around the perimeter of the perovskite-crystalline silicon tandem solar cell in Embodiment 1 of the present invention;
[0027] Figure 7 This is a laser confocal microscope image of the laser-etched edge of the perovskite-crystalline silicon tandem solar cell in Embodiment 1 of the present invention;
[0028] Figure 8 Stability test diagram of laser-assisted encapsulated perovskite-silicon tandem solar cell provided by the present invention;
[0029] In the figure: 1. First metal gate, 2. Crystalline silicon bottom cell, 3. Interconnect layer, 4. First charge transport layer, 5. Perovskite light-absorbing layer, 6. Second charge transport layer, 7. Inner encapsulation buffer layer, 8. Transparent window layer, 9. Second metal gate. Detailed Implementation
[0030] The present invention will now be described in detail with reference to the accompanying drawings. Unless otherwise specified, the features of the following embodiments and implementations can be combined with each other.
[0031] The core idea of this invention is as follows: This invention employs laser edge isolation technology to form protective grooves around the cut surface of the perovskite active layer on the top of the tandem solar cell. This prevents external water and oxygen erosion and damage, reduces the risk of perovskite absorber layer decomposition, and extends the lifespan of the tandem solar cell. Furthermore, the perovskite absorber layer remaining in the area between the protective grooves also prevents the energy emitted by the laser from directly affecting the crystalline silicon bottom cell, reducing damage to the crystalline silicon bottom cell during laser etching and significantly improving the stability of the tandem solar cell. Combining atomic layer deposition (ALD) with internal encapsulation buffer layer technology and laser fine scribing technology reduces the short-circuit risk of the tandem solar cell, prevents conduction between the interconnect layer and the transparent window layer, suppresses carrier recombination, ion migration, and metal gate corrosion in the perovskite light-absorbing layer, reduces the mask deposition difficulty of the interconnect layer and transparent window layer, and achieves excellent encapsulation effects while ensuring the efficiency of the perovskite-crystalline silicon tandem solar cell.
[0032] The technical solution adopted by the present invention is as follows: As a first aspect, such as Figure 1 The diagram shown is for illustrative purposes only and is not intended as a cross-sectional view of the final fabricated tandem solar cell. A perovskite-silicon tandem solar cell based on laser-assisted encapsulation is provided. From bottom to top, the perovskite-silicon tandem solar cell consists of a first metal gate 1, a silicon substrate 2, an interconnect layer 3, a first charge transport layer 4, a perovskite light-absorbing layer 5, a second charge transport layer 6, an inner encapsulation buffer layer 7, a transparent window layer 8, and a second metal gate 9.
[0033] As a second aspect, the present invention also provides a method for fabricating a perovskite-silicon tandem solar cell based on laser-assisted encapsulation, the method comprising the following steps:
[0034] (1) A first metal gate 1 is fabricated on the back side of the crystalline silicon bottom cell 2;
[0035] (2) An interconnect layer 3, a first charge transport layer 4, a perovskite light-absorbing layer 5, and a second charge transport layer 6 are sequentially fabricated on the front side of the crystalline silicon bottom cell 2.
[0036] (4) Use a laser to perform the first edge isolation etching on the four sides of the front of the battery;
[0037] (5) An inner encapsulation buffer layer 7, a transparent window layer 8, and a second metal gate 9 are sequentially fabricated on the front side of the etched battery.
[0038] (6) A laser is used to perform a second edge isolation etching on the four sides of the front of the battery to obtain a complete laser-assisted encapsulated perovskite-crystalline silicon tandem battery.
[0039] Further, the edges of the interconnect layer 3 and transparent window layer 8 are e1 and e2 away from the edge of the crystalline silicon substrate cell 2, where 0 < e1 = e2 < side length of the crystalline silicon substrate cell / 2; the edges of the first edge isolation etching are c1 and c2 away from the edge of the interconnect layer 3 pattern, where 0 < c1 = c2 < e1; the widths of the first edge isolation etching are b1 and b2, where 0 < b1 = b2 < e1; the edges of the second edge isolation etching are d1 and d2 away from the edge of the interconnect layer pattern, where c1 < d1 = d2 < e1; the widths of the second edge isolation etching are a1 and a2, where 0 < a1 = a2 = e1 - d1 < e1 - c1.
[0040] Furthermore, the inner encapsulation buffer layer 7 is one or more composites of tin oxide, zinc oxide, nickel oxide, molybdenum oxide, aluminum oxide, silicon oxide, titanium oxide, vanadium oxide, chromium oxide, manganese oxide, magnesium oxide, lead oxide, germanium oxide, cobalt oxide, cuprous oxide, gallium oxide, zirconium oxide, niobium oxide, indium oxide, antimony oxide, cerium oxide, tantalum oxide, and tungsten oxide.
[0041] Furthermore, the inner encapsulation buffer layer 7 is deposited by atomic layer deposition, chemical vapor deposition, or physical vapor deposition, preferably atomic layer deposition, with a thickness of 0.1–3000 nm.
[0042] Example 1:
[0043] like Figure 2 As shown, a method for fabricating a laser-assisted encapsulated perovskite-silicon tandem solar cell includes the following steps:
[0044] (1) Fabrication of HJT crystalline silicon bottom cells: Commercial-grade G12H N-type silicon wafers with dimensions (210mm × 105mm) were selected, with a resistivity of 4.8 Ω·cm and a thickness of 140 μm. The silicon wafers were sequentially polished, texturized, and cleaned to obtain silicon wafers with textured pyramids. 4 nm thick intrinsic amorphous silicon passivation layers were deposited on both the front and back sides of the silicon wafer using PECVD. A 5 nm thick phosphorus-doped N-type amorphous silicon layer was deposited on the front side of the silicon wafer using PECVD, and a 5 nm thick boron-doped P-type amorphous silicon layer was deposited on the back side of the silicon wafer.
[0045] (2) A 90 nm thick ITO layer is photo-sputtered on the surface of a P-type amorphous silicon layer, and a 10 nm thick ITO interconnect layer is photo-sputtered on the surface of an N-type amorphous silicon layer. The effective coating area of the ITO interconnect layer pattern is 209 mm × 101 mm.
[0046] (3) Silk screen printing low-temperature silver grid on the back of HJT crystalline silicon bottom cell and curing at 190°C for 25 min.
[0047] (4) A NiO first charge transport layer with a thickness of 20 nm is sputtered and deposited on the surface of the ITO interconnect layer. The effective coating area of the first charge transport layer is 210 mm × 105 mm.
[0048] (5) A 900 nm thick Cs layer was deposited on the slit surface of the first charge transport layer of NiO. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 The perovskite light-absorbing layer has an effective coating area of 210mm × 105mm.
[0049] (6) A C60 second charge transport layer with a thickness of 15 nm is vacuum-deposited on the surface of the perovskite light-absorbing layer. The effective coating area of the second charge transport layer is 210 mm × 103 mm.
[0050] (7) A 532nm green picosecond laser was used to perform the first edge isolation etching on the four sides of the front of the battery. The edge of the first edge isolation etching was 0.3mm away from the edge of the interconnect layer pattern. The width of the first edge isolation etching was 0.08mm. The laser power was 13W, the laser pulse width was 1.5ps, the laser frequency was 400kHz, the laser processing speed was 0.1m / s, and the laser focal length was 53mm.
[0051] (8) After the first edge isolation etching, a 20nm thick SnO2 inner encapsulation buffer layer is deposited on the front atomic layer of the battery. The effective coating area of the inner encapsulation buffer layer is 210mm×105mm.
[0052] (9) A 45nm thick IZO transparent window layer is deposited by sputtering on the surface of the SnO2 encapsulation buffer layer. The effective coating area of the IZO transparent window layer pattern is 209mm×101mm.
[0053] (10) Screen print a low-temperature silver grid on the surface of the IZO transparent window layer and cure at 110°C for 10 min.
[0054] (11) A 1064nm infrared nanosecond laser was used to perform a second edge isolation etching on the four sides of the front side of the battery. The edge of the second edge isolation etching was 0.37mm away from the edge of the interconnect layer pattern. The width of the second edge isolation etching was 1.63mm. The laser power was 10W, the laser pulse width was 51ns, the laser frequency was 43kHz, the laser processing speed was 0.1m / s, and the laser focal length was 53mm. Thus, a complete laser-assisted packaged perovskite-crystalline silicon tandem battery was obtained.
[0055] Comparative Example 1:
[0056] like Figure 4As shown, a method for fabricating a conventional perovskite-silicon tandem solar cell includes the following steps:
[0057] (1) Fabrication of HJT crystalline silicon bottom cells: Commercial-grade G12H N-type silicon wafers with dimensions (210mm × 105mm) were selected, with a resistivity of 4.8 Ω·cm and a thickness of 140 μm. The silicon wafers were sequentially polished, texturized, and cleaned to obtain silicon wafers with textured pyramids. 4 nm thick intrinsic amorphous silicon passivation layers were deposited on both the front and back sides of the silicon wafer using PECVD. A 5 nm thick phosphorus-doped N-type amorphous silicon layer was deposited on the front side of the silicon wafer using PECVD, and a 5 nm thick boron-doped P-type amorphous silicon layer was deposited on the back side of the silicon wafer.
[0058] (2) A 90 nm thick ITO layer is photo-sputtered on the surface of a P-type amorphous silicon layer, and a 10 nm thick ITO interconnect layer is photo-sputtered on the surface of an N-type amorphous silicon layer. The effective coating area of the ITO interconnect layer pattern is 209 mm × 101 mm.
[0059] (3) Silk screen printing low-temperature silver grid on the back of HJT crystalline silicon bottom cell and curing at 190°C for 25 min.
[0060] (4) A NiO first charge transport layer with a thickness of 20 nm is sputtered and deposited on the surface of the ITO interconnect layer. The effective coating area of the first charge transport layer is 210 mm × 105 mm.
[0061] (5) A 900 nm thick Cs layer was deposited on the slit surface of the first charge transport layer of NiO. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 The perovskite light-absorbing layer has an effective coating area of 210mm × 105mm.
[0062] (6) A C60 second charge transport layer with a thickness of 15 nm is vacuum-deposited on the surface of the perovskite light-absorbing layer. The effective coating area of the second charge transport layer is 210 mm × 103 mm.
[0063] (7) A SnO2 buffer layer with a thickness of 20 nm is deposited on the surface of the second charge transport layer of C60. The effective coating area of the buffer layer is 210 mm × 105 mm.
[0064] (8) A 45 nm thick IZO transparent window layer is deposited on the surface of the SnO2 buffer layer by mask sputtering. The effective coating area of the IZO transparent window layer pattern is 209 mm × 101 mm.
[0065] (9) A low-temperature silver grid is screen-printed on the surface of the IZO transparent window layer and cured at 110°C for 10 minutes to obtain a complete conventional perovskite-crystalline silicon tandem solar cell.
[0066] Comparative Example 2:
[0067] like Figure 5 As shown, a method for fabricating a non-laser-assisted encapsulated perovskite-silicon tandem solar cell includes the following steps:
[0068] (1) Fabrication of HJT crystalline silicon bottom cells: Commercial-grade G12H N-type silicon wafers with dimensions (210mm × 105mm) were selected, with a resistivity of 4.8 Ω·cm and a thickness of 140 μm. The silicon wafers were sequentially polished, texturized, and cleaned to obtain silicon wafers with textured pyramids. 4 nm thick intrinsic amorphous silicon passivation layers were deposited on both the front and back sides of the silicon wafer using PECVD. A 5 nm thick phosphorus-doped N-type amorphous silicon layer was deposited on the front side of the silicon wafer using PECVD, and a 5 nm thick boron-doped P-type amorphous silicon layer was deposited on the back side of the silicon wafer.
[0069] (2) A 90 nm thick ITO layer is photo-sputtered on the surface of a P-type amorphous silicon layer, and a 10 nm thick ITO interconnect layer is photo-sputtered on the surface of an N-type amorphous silicon layer. The effective coating area of the ITO interconnect layer pattern is 209 mm × 101 mm.
[0070] (3) Silk screen printing low-temperature silver grid on the back of HJT crystalline silicon bottom cell and curing at 190°C for 25 min.
[0071] (4) A NiO first charge transport layer with a thickness of 20 nm is sputtered and deposited on the surface of the ITO interconnect layer. The effective coating area of the first charge transport layer is 210 mm × 105 mm.
[0072] (5) A 900 nm thick Cs layer was deposited on the slit surface of the first charge transport layer of NiO. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 The perovskite light-absorbing layer has an effective coating area of 210mm × 105mm.
[0073] (6) A C60 second charge transport layer with a thickness of 15 nm is vacuum-deposited on the surface of the perovskite light-absorbing layer. The effective coating area of the second charge transport layer is 210 mm × 103 mm.
[0074] (7) A SnO2 buffer layer with a thickness of 20 nm is deposited on the surface of the second charge transport layer of C60. The effective coating area of the buffer layer is 210 mm × 105 mm.
[0075] (8) A 45 nm thick IZO transparent window layer is deposited on the surface of the SnO2 buffer layer by mask sputtering. The effective coating area of the IZO transparent window layer pattern is 209 mm × 101 mm.
[0076] (9) Silk screen printing low-temperature silver grid on the surface of IZO transparent window layer and curing at 110℃ for 10 min.
[0077] (10) A 1064nm infrared nanosecond laser was used to perform a second edge isolation etching on the four sides of the front side of the battery. The edge of the second edge isolation etching was 0.37mm away from the edge of the interconnect layer pattern. The width of the second edge isolation etching was 1.63mm. The laser power was 10W, the laser pulse width was 51ns, the laser frequency was 43kHz, the laser processing speed was 0.1m / s, and the laser focal length was 53mm. Thus, a complete non-laser-assisted packaged perovskite crystalline silicon tandem battery was obtained.
[0078] Table 1: Performance Parameters of Devices in Example 1 and Comparative Example
[0079]
[0080] like Figure 6 As shown, the perovskite-crystalline silicon tandem solar cell prepared in Example 1 has a clear edge-isolated etched area around its perimeter, and the surface is clean. The laser-etched edges were observed using a laser confocal microscope (see...). Figure 7 It can be concluded that laser edge isolation did not produce a significant edge heat-affected zone, and an effective inner encapsulation buffer layer was formed within the groove of the first laser edge isolation etching interface. (See Table 1 for battery test area of 211.09 cm²). 2 )and Figure 8As shown, the photoelectric conversion efficiency of the perovskite-silicon tandem solar cell prepared in Example 1 is comparable to that of the tandem solar cell prepared in the comparative example, indicating that the low-damage laser-assisted encapsulation technology does not lead to a significant reduction in the performance of the tandem solar cell. More importantly, the stability of the perovskite-silicon tandem solar cell prepared with laser-assisted encapsulation is far superior to that of the tandem solar cell prepared in the comparative example, and the efficiency of the cell only decreases by 5.1% after 1000 hours of maximum power point tracking. The encapsulation structure prepared by the above process can effectively seal the edges of the tandem solar cell, isolating the tandem solar cell from moisture and oxygen in the air, effectively improving the sealing performance of the tandem solar cell edges, and providing effective water and oxygen protection for the core structure of the tandem solar cell. In addition, laser edge isolation can achieve complete insulation between the interconnect layer and the transparent window layer, reducing the risk of short circuits in the tandem solar cell caused by mask misalignment deposition, and improving the consistency of the tandem solar cell fabrication process. It should be noted that the first laser edge isolation helps to deposit the inner encapsulation buffer layer, achieving a tight fit between the buffer layer and the edge of the perovskite active layer. The second laser edge isolation is used to remove the edge portions of the battery, preventing edge leakage, and to remove excess irregularities at the edge of the buffer layer, forming a better moisture barrier. Therefore, the distance of the second laser scribing must be smaller than that of the first laser scribing to prevent the edge portions of the buffer layer from being exposed due to an excessively wide distance in the second laser scribing, which would damage the buffer layer encapsulation structure. The encapsulation method provided in this application is characterized by its simple process, low cost, and ease of implementation in large-scale industrial production.
[0081] The above description is merely a preferred experimental example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A perovskite-silicon tandem solar cell based on laser-assisted encapsulation, characterized in that, The perovskite-silicon tandem solar cell, from bottom to top, consists of a first metal gate (1), a crystalline silicon base cell (2), an interconnect layer (3), a first charge transport layer (4), a perovskite light-absorbing layer (5), a second charge transport layer (6), an inner encapsulation buffer layer (7), a transparent window layer (8), and a second metal gate (9). The inner encapsulation buffer layer (7) covers the interconnect layer (3), the first charge transport layer (4), the perovskite light-absorbing layer (5), the second charge transport layer (6), and the second charge transport layer (6) above the second charge transport layer (6). The side lengths of the interconnect layer (3), the first charge transport layer (4), the perovskite light-absorbing layer (5), and the second charge transport layer (6) covered by the inner encapsulation buffer layer (7) are all smaller than the side length of the crystalline silicon base cell (2).
2. The perovskite-silicon tandem solar cell as described in claim 1, characterized in that, The side lengths of the interconnect layer (3) and the transparent window layer (8) are smaller than the side lengths of the crystalline silicon bottom cell (2), the first charge transport layer (4), the perovskite light-absorbing layer (5), and the second charge transport layer (6).
3. A method for fabricating a perovskite-silicon tandem solar cell based on laser-assisted encapsulation, characterized in that, Includes the following steps: A first metal gate (1) is fabricated on the back side of a crystalline silicon bottom cell (2); An interconnect layer (3), a first charge transport layer (4), a perovskite light-absorbing layer (5), and a second charge transport layer (6) are sequentially fabricated on the front side of a crystalline silicon bottom cell (2). The first edge isolation etching is performed around the front of the battery using laser; An inner encapsulation buffer layer (7), a transparent window layer (8), and a second metal gate (9) are sequentially fabricated on the front side of the etched battery. A second edge isolation etching is performed around the front of the battery using laser; The inner encapsulation buffer layer (7) covers the periphery of the interconnect layer (3), the first charge transport layer (4), the perovskite light-absorbing layer (5), the second charge transport layer (6), and the second charge transport layer (6). The side lengths of the interconnect layer (3), the first charge transport layer (4), the perovskite light-absorbing layer (5), and the second charge transport layer (6) covered by the inner encapsulation buffer layer (7) are all smaller than the side length of the crystalline silicon bottom cell (2).
4. The preparation method according to claim 3, characterized in that, The edges of the interconnect layer (3) and transparent window layer (8) are e1 and e2 away from the edge of the crystalline silicon substrate cell (2), respectively, where 0 < e1 = e2 < side length of crystalline silicon substrate cell (2) / 2.
5. The preparation method according to claim 3, characterized in that, The edge distance of the first edge isolation etching from the edge of the interconnect layer (3) pattern is c1 and c2, where 0 < c1 = c2 < e1.
6. The preparation method according to claim 3, characterized in that, The widths of the first edge isolation etching are b1 and b2, where 0 < b1 = b2 < e1.
7. The preparation method according to claim 3, characterized in that, The edge distance of the second edge isolation etching from the edge of the interconnect layer (3) pattern is d1 and d2, where c1 < d1 = d2 < e1.
8. The preparation method according to claim 3, characterized in that, The widths of the second edge isolation etching are a1 and a2, where 0 < a1 = a2 = e1 - d1 < e1 - c1.
9. The preparation method according to claim 3, characterized in that, The inner encapsulation buffer layer (7) is one or more of the following compounds: tin oxide, zinc oxide, nickel oxide, molybdenum oxide, aluminum oxide, silicon oxide, titanium oxide, vanadium oxide, chromium oxide, manganese oxide, magnesium oxide, lead oxide, germanium oxide, cobalt oxide, cuprous oxide, gallium oxide, zirconium oxide, niobium oxide, indium oxide, antimony oxide, cerium oxide, tantalum oxide, and tungsten oxide.
10. The preparation method according to claim 3, characterized in that, The inner encapsulation buffer layer (7) is deposited by atomic layer deposition, chemical vapor deposition or physical vapor deposition, and has a thickness of 0.1~3000 nm.
Citation Information
Patent Citations
Perovskite copper-indium-gallium-selenium laminated cell and preparation method thereof
CN116096113A
Perovskite laminated module crystalline silicon triple-laminated solar cell and preparation method thereof
CN118019365A